Premature Ventricular Complex Causing Ice-Pick Headache - Selcuk Ozturk; Ertan Yetkin (Case Reports in Cardiology)
Ice pick headache is a momentary, transient, repetitive headache disorder and manifests with the stabbing pains and jolts. The exact mechanism causing this disease is unknown. Premature ventricular contractions are early depolarization of the ventricular myocardium and in the absence of a structural heart disease, it is considered to be a benign disease. In this report, we describe a male patient presenting with the symptom of momentary headache attacks accompanied with instant chest pain which is associated with premature ventricular contraction.